Peranan Guru Fiqih Terhadap Pembinaan Sholat Berjama’ah Siswa Kelas IX MTs Jam’iyah Mahmudiyah Desa Batu Melenggang - Hayatun_ Sabariah; Ima Sari Ramadhani; Sindi Pramita; Mudrika Hanim (Tarbiatuna: Journal of Islamic Education Studies, 2021)
This research uses 3 stages, namely; the research instrument preparation stage, the research instrument trial stage, the research implementation stage. The subjects of this study were teachers and students of MTs Jam'iyah Mahmudiyah Batu Melenggang Village. Data collection techniques used interviews, observations, document research, literature studies and questionnaires/questionnaires. Fiqh Learning Process at MTs Jam'iyah Mahmudiyah Batu Melenggang V0illage .which has an average result of 55.63, a median of 54.17, a mode of 50.5, a variant of 91.32 and a standard deviation of 9.55 acceptable with a significance limit of good tolerance and meets the criteria. Congregational Prayer Guidance for Class IX Students at MTs Jam'iyah Mahmudiyah Batu Melenggang Village has an average result of 66.27, a median of 56.62, a mode of 58.06, a variant of 28.27 and a standard deviation of 5.32 accepted with a tolerance significance limit. There is a significant relationship between the role of the Fiqh teacher on the formation of congregational prayer for Class IX students at MTs Jam'iyah Mahmudiyah in Batu Melenggang Village with the results of Fcount = 10,903 and Ftable (1.31) (0.01) = 7.53 which can be concluded Fcount≥Ftable by accepting Ha and rejecting H0 with the regression line equation of 49.55+0.29 X.